Potential in vitro anti-periodontopathogenic, anti-Chikungunya activities and in vivo toxicity of Brazilian red propolis - Silva, Nagela Bernadelli Sousa; de Souza, Jonathan Henrique; Santiago, Mariana Brentini; da Silva Aguiar, Jhennyfer Rodrigues; Martins, Daniel Oliveira Silva [UNESP]; da Silva, Rafael Alves; de Andrade Santos, Igor; Aldana-Mejía, Jennyfer A.; Jardim, Ana Carolina Gomes [UNESP]; dos Santos Pedroso, Reginaldo; Ambrósio, Sergio Ricardo; Veneziani, Rodrigo Cássio Sola; et al. (Springer Nature, 2022)
Bacterial and viral infections are serious public health issue. Therefore, this study aimed to evaluate the antibacterial, antibiofilm and antiviral potential of the Brazilian Red Propolis (BRP) crude hydroalcoholic extract, fractions, and isolated compounds, as well as their in vivo toxicity. The antibacterial activity was evaluated by determining the Minimum Inhibitory Concentration and the antibiofilm activity by determining the Minimum Inhibitory Concentration of Biofilm (MICB50). The viable bacteria count (Log10 UFC/mL) was also obtained. The antiviral assays were performed by infecting BHK-21 cells with Chikungunya (CHIKV) nanoluc. The toxicity of the BRP was evaluated in the Caenorhabditis elegans animal model. The MIC values for the crude hydroalcoholic extract sample ranged from 3.12 to 100 μg/mL, while fractions and isolated compounds the MIC values ranged from 1.56 to 400 μg/mL.The BRP crude hydroalcoholic extract, oblongifolin B, and gutiferone E presented MICB50 values ranging from 1.56 to 100 μg/mL against monospecies and multispecies biofilms. Neovestitol and vestitol inhibited CHIKV infection by 93.5 and 96.7%, respectively. The tests to evaluate toxicity in C. elegans demonstrated that the BRP was not toxic below the concentrations 750 μg/mL. The results constitute an alternative approach for treating various infectious diseases.